LEGALITY OF ALCOHOLIC BEVERAGES IN INDONESIA: BETWEEN POLITICAL ECONOMY AND HIFZ AL-ʿAQL PERSPECTIVE - Beni Firdaus; Busyro Busyro; Ismail Ismail; Rahmiati Rahmiati; Pendi Hasibuan; Selfia Marlina (Universitas Syiah Kuala, 2023)
Legalizing alcoholic beverages under Indonesian Presidential Decree Number 10 of 2021 concerning to Investment Business raises conflicting view with Islamic norms in Indonesian as religious state. Under Islamic norm such prohibition intended to maintaining of reason (ḥifẓ al-ʿaql), while on the one hand it is for the improvement of the country’s economy (ḥifẓ al-mal). This paper measures such contradictory under maqasid Syariah auspice. The method used is a normative research with a content analysis approach. This paper found that the legalization of investment in alcoholic beverages has not reached to the stage of necessity (ḍaruriyya), while the acquisition of property (ḥifẓ al-mal) was obtained through the legalization of alcoholic beverage investments, only at the level of (taḥsiniyyah). Therefore, something related to the tahsiniya level should not negate the position of ḍaruriyya of ḥifẓ al-ʿaql. Eliminating the potential of greater mafsadah must be put forward by the Indonesian government rather than producing uncertain maslahah.